The private charities and the education and training working in Spain (1899-1972) - Leoncio VEGA GIL (Historia de la Educación, 2013)
The work talks about social and pedagogical contribution of private Spanish charities to social integraation and training of working in the 20th century, in addition to include this private initiatives as complementary elements of national system of education.